Comparison of Revision Rates and Clinical Outcomes between Anatomic and Reverse Total Shoulder Arthroplasty for Rotator Cuff-Intact Osteoarthritis: A Systematic Review and Meta-Analysis - Thamrongskulsiri, Napatpong; Limskul, Danaithep; Tanpowpong, Thanathep; Kuptniratsaikul, Somsak; Itthipanichpong, Thun (Clinics in orthopedic surgery, 2025)
Background: This study aimed to compare the outcomes of reverse total shoulder arthroplasty (rTSA) and anatomic total shoulder arthroplasty (aTSA) in patients with rotator cuff-intact osteoarthritis, assessing revision and complication rates, patient-reported outcomes, and postoperative range of motion. Methods: This systematic review and meta-analysis included comparative studies with levels I–III evidence that assessed rTSA and aTSA in patients with rotator cuff–intact osteoarthritis. Inclusion criteria required studies to report postoperative revision rates, complication rates, patient-reported outcomes, or range of motion with a minimum follow-up of 2 years. Studies focusing on noncomparative designs, biomechanical analyses, or case series were excluded. A comprehensive search of PubMed, Ovid Medline, and Scopus databases was conducted from their inception through December 2024. Odds ratios (ORs) with 95% CI were used for dichotomous outcomes, and mean differences (MDs) with 95% CI were used for continuous outcomes. Results: A total of 14 studies, encompassing 4,819 cases, were included in the analysis. rTSA demonstrated a significantly lower revision rate compared to aTSA (OR, 0.43; 95% CI, 0.29 to 0.65; p < 0.001), while both procedures yielded similar Constant scores (MD, –2.23; 95% CI, –5.80 to 1.33; p = 0.22), simple shoulder test (MD, 0.11; 95% CI, –0.30 to 0.52; p = 0.59), American Shoulder and Elbow Surgeons scores (MD, –1.51; 95% CI, –4.91 to 1.90; p = 0.39), subjective shoulder values (MD, 2.16; 95% CI, –2.44 to 6.75; p = 0.36), visual analog scale for pain (MD, –0.25; 95% CI, –0.72 to 0.21; p = 0.29), and ranges of motion, except for external rotation, where aTSA demonstrated superiority (MD, –11.28; 95% CI, –14.95 to –7.61; p < 0.001). Conclusions: In patients with rotator cuff-intact osteoarthritis, rTSA is associated with a lower revision rate compared to aTSA, while achieving comparable clinical outcomes and range of motion, with the exception of external rotation. KCI Citation Count: 0